Prevalence and Pathogenic Potential of Campylobacter Isolates from Free-Living, Human-Commensal American Crows - Weis, Allison M. (American Society for Microbiology, 2014)
Recent studies have suggested a potential role for wild birds in zoonotic transmission of Campylobacter jejuni, the leading cause of gastroenteritis in humans worldwide. In this study, we detected Campylobacter spp. in 66.9% (85/127) of free-ranging American crows (Corvus brachyrhyncos) sampled in the Sacramento Valley of California in 2012 and 2013. Biochemical testing and sequence analysis of 16S rRNA revealed that 93% of isolates (n = 70) were C. jejuni, with cytolethal distending toxin (CDT) and flagellin A genes detected by PCR in 20% and 46% of the C. jejuni isolates (n = 59), respectively. The high prevalence of C. jejuni, coupled with the occurrence of known virulence markers CDT and flagellin A, demonstrates that crows shed Campylobacter spp. in their feces that are potentially pathogenic to humans. Crows are abundant in urban, suburban, and agricultural settings, and thus further study to determine their role in zoonotic transmission of Campylobacter will inform public health.